(untitled) (Research, Society and Development, 2021)
Endometriosis is a gynecological disease characterized by the presence of endometrium as tissue-epithelium and stroma that develops outside the uterine cavity. It is a chronic, estrogen-dependent disease, is associated with pelvic pain, dysmenorrhea, dyspareunia and infertility. Given the great impact of this disease on the quality of life of women, there has been a growing interest in the discovery of new drugs that are more effective, tolerability and safety. For this, a literature review was carried out from articles published between 2008 and 2018 available regarding pharmacological treatments for endometriosis in the SCIENCE DIRECT and PUBMED databases. A total of 223 articles published in the last 10 years were found in "Portuguese and English". After evaluating the articles, 15 articles were selected for the present study, which complied with all the eligibility criteria proposed in the methodology. It was concluded that we can count on several types of treatments for endometriosis, but most have the objective of treating the symptoms associated with endometriosis. Currently, the specific treatment we can count on is dienogeste. In addition, there are many studies in search of new drugs and promising treatments for this pathology. Thus, more research is needed regarding the theme and that the pharmacist plays a fundamental role in the adherence to the patient’s treatment.